(untitled) (KASBIT Business Journal, 2020)
Liquidity management is a crucial decision in commercial banking operations especially when the depositors need cash daily. A sound liquidity policy may not only enhance the efficiency of a bank’s operations but also may impact its customer retention. The study, therefore, is focused to investigate the capacity of bank-specific forces like capital adequacy and management quality for explaining the commercial bank’s liquidity decision in Pakistan. This empirical research study uses the financial statements of 23 commercial banks with eleven years’ frequency; 2008-2018. The study employs the panel-data modeling and estimation method for the analysis of relevant data. Bank’s liquidity management decision was used as the outcome variable while the independent variables were capital adequacy ratio and management quality ratio. The funding cost ratio, profitability ratio, deposit ratio, and non-performing loan ratio were used as the control variable. This empirical research finds that the commercial bank’s liquidity decision is strongly supported due to increments in capital adequacy ratio as well as in management quality ratio while funding cost ratio and non-performing loans significantly reduce the existing level of liquidity in commercial banks of Pakistan. The study contributes to the understanding of liquidity decisions not only in Pakistan but also in other countries in the Asian-region. The factors used for explaining liquidity decisions of the banking sector in this study are not necessarily the only factors in this domain but may include further industry-based, firm-specific based, and macro-level factors in future research. However, the policymakers in the commercial banking sector of Pakistan are recommended to consider the significant factors of this study while deciding on setting an appropriate level of liquidity in their banks for the proper functioning of their day to day operations.